The effect of erythropoietin on creatine phosphokinase levels during ischemia reperfusion injury in rats - Constantinos Tsompos; Constantinos Panoulis; Konstantinos Toutouzas; George Zografos; Apostolos Papalois (Revista Cubana de Medicina Militar)
Objective: to examine the effect of erythropoietin testing on rat model and particularly the ischemia reperfusion protocol. Methods: experimental study of 40 rats weighing 247.7 g as average. The beneficial effect or non-effectiveness of the erythroproietin molecule on the blood creatine phosphokinase levels was biochemically studied. It was measured 60 min (groups A and C) and 120 min (groups B and D) after reperfusion with no administration of erythropoietin in groups C and D. Results: Erythropoietin administration significantly increased the creatine phosphokinase levels to 3586.05 IU/L (1873.115 IU/L-5298.985 IU/L;p= 0.0001). This finding was in accordance with the result of paired t-test (p= 0.0001). Reperfusion time significantly increased the CPK levels to 557.35 IU/L (-1513.284 IU/L-2627.984 IU/L; p= 0.5890), also in accordance with paired t-test (p= 0.4661). The interaction of erythropoietin administration and reperfusion time significantly increased the creatine phosphokinase levels to 1988.282 IU/L (918.2646 IU/L-3058.299 IU/L; p= 0.0006). Conclusions: Erythropoietin administration, reperfusion time and their interaction generally increase short-term effects on blood creatine phosphokinase after ischemia reperfusion injury.